Green Performance Management and Organizational Agility of Multinational Oil and Gas Companies in Nigeria - Akpobolokami, Andy Mezeh (Journal of Strategic Management, 2022)
This study examined the relationship between green performance management and organizational agility of multinational oil and gas companies in Nigeria. The study adopted the cross-sectional research survey design. Primary data was generated through structured questionnaire. The population of this study was the five (5) International (Multinational) Oil and Gas producing companies in Nigeria registered with the Department of Petroleum Resources. A census sampling was adopted hence, the entire five (5) International (Multinational) Oil and Gas producing companies in Nigeria were studied. However, for the purposes of data collection, 50 managers were used as respondents. The reliability of the instrument was achieved by the use of the Cronbach Alpha coefficient with all the items scoring above 0.70. The hypotheses were tested using the Spearman’s Rank Order Correlation Statistics while the partial correlation was used to test the moderating influence of green work perceptions. The tests were carried out at a 0.05 significance level. Findings revealed that there is a significant relationship green performance management and organizational agility of multinational oil and gas companies in Nigeria. Therefore, this study concludes that the adoption of green performance management positively enhances organizational agility of multinational oil and gas companies in Nigeria through flexibility, adaptive capacity and sensitivity. Therefore, the study recommends that Management of multinational oil and gas companies should have proper communication of green schemes across the organization. This is important as it ensures that every employee is informed of the expected standards of performance. Keywords: Green Performance Management, Organizational Agility, Flexibility, Adaptability, Sensitivity